A framework for an interactive project scheduling system under limited resources - (:unkn) unknown (ELSEVIER SCIENCE BV, 1996)
In this paper, we propose a framework for an interactive project scheduling system under limited resources. The framework includes a modelling module (MODEL) and a scheduling module (SCHEDULER). The modelling module MODEL allows the Decision Maker (DM) to develop his/her own model with features such as alternative operating modes for activities; renewable, nonrenewable and/or doubly-constrained resource constraints; general cash flow patterns, related to the realization of activities or events; and progress payments distributed over the project span. The performance criteria include the maximization of Net Present Value (NPV), and either the minimization of maximum tardiness (when a project due date exists) or the minimization of the project duration (when there is no project due date). The SCHEDULER is developed on a constraint-based scheduling algorithm, which is called Local Constraint Based Analysis (LCBA) and which has previously been tested and shown to produce near-optimal results with respect to the criterion of minimizing project duration. The decisions taken in the SCHEDULER consist Of determining the start times of activities and the specific operating modes in which they are to be realized. The decisions are taken by activating relevant essential conditions in LCBA and in cases where resource conflicts are not resolved, the DM reaches a final decision by testing the alternatives proposed by LCBA through a what-if routine. The SCHEDULER represents a realistic scheduling system which is useful not only in the planning phase of a project but can also be employed during the progress of a project for updating the project plan, if necessary, An important feature is that the project plan can be updated by performing the least modification of future commitments. It is possible to freeze the activities already scheduled in the near future while admitting the changes in the activity/network information.
Keywords: project scheduling; resource constraints; modeling framework; NET PRESENT VALUE; HEURISTIC PERFORMANCE; PROGRAMMING APPROACH; CASH FLOWS; MAXIMIZE; RESTRICTIONS; CONSTRAINTS